On the complex H-bonding network in paravauxite, Fe2+Al2(PO4)2(OH)2·8H2O: A single-crystal neutron diffraction study. (August 2014) - Gatta, G. D.; Vignola, P.; Meven, M.
Abstract: The crystal structure and the chemical composition of a paravauxite from the Siglo Veinte Mine, Llallagua, Bustillo Province, Potosi Department, Bolivia [ Fe (Fe0.916 2+ Mn0.016 2+ Mg0.064 Ca0.002 )∑0.998 Al (1) Al (2) Al2.005 P (P1.998 Si0.002 )∑2 O8 (OH)2 ·8H2 O, a = 5.242(1) Å, b = 10.569(2) Å, c = 6.970(2) Å, α = 106.78(3)°, β = 110.81(2)° and γ = 72.29(2)°, space group P ], was investigated by single-crystal neutron diffraction and electron microprobe analysis in wavelength-dispersive mode. Neutron-intensity data were collected at 293 K and anisotropic structure refinement was performed. At the end of the refinement no peak larger than ±1.3 fm/Å 3 was present in the final difference-Fourier map of the nuclear density. The final statistical index was R 1 = 0.0495 for 194 refined parameters and 1678 unique reflections with F o > 4σ( F o ). Eleven independent H sites (i.e. H (1), H (2), H (3), H (4A), H (4B), H (5), H (6), H (7), H (8), H (9A) and H (9B)), all at ∼1 Å from the respective O sites, were located successfully. H(4A) and H(4B) and H(9A) and H(9B) are two mutually exclusive subsite couples only 0.4−0.6 Å apart. The complex H-bonding scheme in the paravauxite structure is now well defined and 12 independent H bonds, with an energetically favourable bonding configuration, are described. A comparison between the previous experimental findings based on Raman and infrared spectroscopy and those obtained in this present study is carried out. Paravauxite provides the rare opportunity to investigate the H-bond configuration of coexisting hydroxyl groups and H2 O molecules in minerals by single-crystal neutron diffraction. H2 O is present as zeolitic (i.e. lying in the cavities) and non-zeolitic H2 O (i.e. bonded to Al or Fe to form Al or Fe octahedra).